COMPARATIVE ANALYSIS OF PUBLIC HEALTH SERVICE QUALITY BETWEEN JAPAN’S KOKUMIN KENKOU HOKEN AND INDONESIA’S BPJS KESEHATAN - Suryani, Riza Adelia (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2025)
The purpose of this study is to compare the health service systems of Kokumin Kenkou Hoken (KKH) in Japan and BPJS Kesehatan in Indonesia as representations of developed and developing countries. The research problem focuses on the disparities in effectiveness, efficiency, and service quality resulting from differences in infrastructure, financing mechanisms, and technological adoption in both countries. The analysis is grounded in comparative public administration theory and the service quality framework proposed by Zeithaml et al. This study employs a qualitative method through an extensive literature review of regulations, official reports, and recent scholarly findings related to national health insurance systems. The results indicate that KKH outperforms in efficiency, technological integration, such as Electronic Medical Records (EMR) and sustainable financing supported by a 50% government subsidy, while BPJS continues to struggle with financing deficits, service inequality, and limited infrastructure despite adopting digital tools such as the Mobile JKN application and the VClaim system. The study recommends strengthening digital health infrastructure, improving public digital literacy, and enhancing international collaboration to support more inclusive and equitable health service delivery in Indonesia.